Implementasi Model Pembelajaran Experiential Learning untuk Meningkatkan Hasil Belajar Seni Budaya Siswa Sekolah Dasar - Tika Puspita Sari; Yani Timor Prajawati; Indah Zulhidayati; Lutfia Okta Riwayati (SEMESTA: Jurnal Ilmu Pendidikan dan Pengajaran, 2026)
This study aims to improve the learning outcomes of Grade V students (n=49) in Cultural Arts, particularly dance, through the implementation of the Experiential Learning model at SD Negeri 16 Cakranegara. The low classical completeness rate of 37% in the pre-cycle stage served as the background of this study. The Experiential Learning model was selected because it emphasizes direct experience as the core of the learning process, which aligns with the students' dominant kinesthetic intelligence. This study employed Classroom Action Research (CAR) based on the Kemmis and McTaggart model, conducted in two cycles, each comprising the stages of planning, implementation, observation, and reflection. Data were collected through observation, learning outcome tests, motivation questionnaires, interviews, and documentation, then analyzed using descriptive statistics with a success indicator of ≥80%. The results demonstrated a consistent improvement from 37% in the pre-cycle to 69% in Cycle I, and 92% in Cycle II, indicating that the Experiential Learning model is effective in improving dance learning outcomes in elementary school in accordance with students' kinesthetic intelligence.